Effectiveness of Intense Pulsed Light (IPL) in Meibomian Gland Dysfunction Related Dry Eye: A Systematic review - Ida Ayu Bintang Maui Putri; Anak Agung Avrella Shora Yuananda; Ni Nyoman Adi Widiastuti (International Medical Journal Corp. Ltd, 2026)
Background: Meibomian gland dysfunction (MGD) is a major contributor to evaporative dry eye disease and is characterized by obstruction of the meibomian gland ducts and altered meibum secretion. These abnormalities disrupt the tear film lipid layer, increase tear evaporation, and contribute to ocular surface inflammation and dry eye symptoms. Intense pulsed light (IPL) has emerged as a procedural treatment for MGD-related dry eye, but existing studies vary in treatment protocols, adjunctive procedures, comparators, and outcome measures. Objective: This systematic review aimed to evaluate the effectiveness and safety of intense pulsed light in patients with meibomian gland dysfunction-related dry eye. Methods: A systematic review was conducted in accordance with the PRISMA 2020 statement. Literature searches were performed in PubMed, Scopus, and ScienceDirect, with the final search completed on May 18, 2026. Eligible studies included original human clinical studies evaluating IPL in patients with MGD-related dry eye. Studies assessing IPL alone, IPL combined with meibomian gland expression, IPL combined with low-level light therapy, or comparisons between IPL devices were included. The primary outcomes of interest were dry eye symptoms, tear film stability, meibomian gland function, inflammatory or mechanistic outcomes, and safety. Two reviewers independently performed study selection, data extraction, and risk of bias assessment. Because of substantial heterogeneity in study design, treatment protocol, comparator type, and outcome reporting, the findings were synthesized qualitatively. Results: The database search identified 660 records. After duplicate removal, title and abstract screening, and full-text assessment, 13 studies were included in the final qualitative synthesis. The included studies consisted of randomized controlled trials, randomized paired-eye studies, prospective comparative studies, prospective interventional studies, and mechanistic clinical studies. Overall, IPL was associated with improvement in tear film stability and meibomian gland-related outcomes, including tear breakup time, non-invasive tear breakup time, lipid layer thickness, meibum quality, gland expressibility, and lid margin abnormalities. Patient-reported symptoms also improved in many studies, although symptom outcomes were less consistent across controlled trials than objective tear film and gland-related parameters. Mechanistic studies reported reductions in inflammatory mediators, including IL-17A, IL-6, PGE2, IL-1β, IL-17F, and MMP-9, suggesting a possible anti-inflammatory effect of IPL. Safety findings were generally favorable, with no consistent reports of serious adverse events. Reported adverse effects were mostly mild and transient, including pain, burning sensation, and isolated partial eyelash loss. Conclusion: Current evidence suggests that IPL is an effective and generally well-tolerated treatment for MGD-related dry eye, particularly for improving tear film stability and meibomian gland function. Symptom improvement is commonly reported but less consistent than objective clinical improvement. Because several studies evaluated IPL in combination with meibomian gland expression or low-level light therapy, the independent effect of IPL should be interpreted cautiously. Further high-quality randomized controlled trials with standardized IPL protocols, longer follow-up, consistent outcome measures, and systematic safety reporting are needed.